Microbial Fuel Cell: Recent Developments in Organic Substrate Use and Bacterial Electrode Interaction - Fatin Syahirah Fadzli; Showkat Ahmad Bhawani; Rania Edrees Adam Mohammad (Journal of Chemistry)
A new bioelectrochemical approach based on metabolic activities inoculated bacteria, and the microbial fuel cell (MFC) acts as biocatalysts for the natural conversion to energy of organic substrates. Among several factors, the organic substrate is the most critical challenge in MFC, which requires long-term stability. The utilization of unstable organic substrate directly affects the MFC performance, such as low energy generation. Similarly, the interaction and effect of the electrode with organic substrate are well discussed. The electrode-bacterial interaction is also another aspect after organic substrate in order to ensure the MFC performance. The conclusion is based on this literature view; the electrode content is also a significant challenge for MFCs with organic substrates in realistic applications. The current review discusses several commercial aspects of MFCs and their potential prospects. A durable organic substrate with an efficient electron transfer medium (anode electrode) is the modern necessity for this approach.